Grammar buzz: let's buzz with grammar / Geraldine de Mello...[et al.] - de Mello, Geraldine; Husin @ Ma'mor, Misyana Susanti; Omar, Nur Hidayatulshima; Ariffin, Kamisah; Md Razak, Mohamad Idham (Universiti Teknologi MARA Shah Alam, 2018)
Grammar Buzz (GB) is an edutainment board game that helps to promote students' grammar acquisition and their ability of using English grammar in sentences. It is a multisensory game which requires players to physically throw the dice and move the token to the phrase category destination. Then the players are to construct a grammatically correct sentence using the phrase category. Students who have difficulty with single-modality learning method would benefit from this visual, kinaesthetic and auditory board game as GB supports intentional grammar learning. While the players are doing something fun, they can be learning grammar without noticing it. Past studies found revamping the delivery of grammar lesson to be fun and enjoyable, helped increase learners' motivation and also interest. Inspired from the Monopoly board game, GB is definitely a creative and innovative alternative to dreary grammar drills. Games can remove boredom without sacrificing repetition that is necessary for successful learning of language elements, especially grammar. GB certainly brings about fun and excitement amongst the players and offers entertaining language practices other than the traditional pencil-paper grammar exercises. GB has huge potential to be commercialized in schools as it is applicable for both students and teachers in schools and also at tertiary level.